Analysis of The Tiktok Social Media Phenomenon For Students: A Case Study of The Millennial Generation - Syarifuddin Syarifuddin; Sigit Triyono; Fatwa Nur'aini; Sovia Husni Rahmia; Rusmaniah Rusmaniah (Program Studi Pendidikan IPS, 2025)
The social media application TikTok, especially among millennial college students, has experienced a surge in popularity in recent years. With the number of downloads continuing to increase, TikTok offers a wide variety of engaging content that captivates a wide audience. This research aims to explore the impact of the use of TikTok on students, not only as a means of entertainment, but also in social, psychological, and cultural contexts. This research method involved interviews with 15 college students and meta-analysis of 20 relevant articles, to gain deeper insights into user interactions with the platform. The findings suggest that the use of TikTok can have a double impact. On the one hand, the platform serves as a tool to strengthen social relationships, increase creativity, and allow for positive self-expression, especially for college students who use it for constructive purposes. On the other hand, overuse can harm academic productivity, trigger social anxiety, sleep disturbances, and decreased mental health. Therefore, it is important for students to manage their time and content consumption on TikTok wisely, in order to minimize negative impacts, while taking advantage of the social and creative potential offered by this application. This research is expected to contribute to understanding the influence of TikTok on students' lifestyles and social interactions in the digital era.